2010
DOI: 10.3233/jad-2010-100462
|View full text |Cite
|
Sign up to set email alerts
|

Apical-to-Basolateral Transport of Amyloid-β Peptides through Blood-Brain Barrier Cells is Mediated by the Receptor for Advanced Glycation End-Products and is Restricted by P-Glycoprotein

Abstract: Several studies have highlighted the close relationship between Alzheimer's disease (AD) and alterations in the bidirectional transport of amyloid-β (Aβ) peptides across the blood-brain barrier (BBB). The brain capillary endothelial cells (BCECs) that compose the BBB express the receptors and transporters that enable this transport process. There is significant in vivo evidence to suggest that P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP) restrict Aβ peptides entry into the brain, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 31 publications
(64 reference statements)
6
97
0
3
Order By: Relevance
“…Furthermore, Pgp may function independently of LRP-1 by limiting the influx of blood-borne Ab into the brain. 67 The pathways governing influx will be described in the next section. The cellular prion protein 68 and the multidrug transporters ABCG2 and 4 have also been shown to contribute to Ab efflux across the BBB, 69 although AD-relevant changes of these are presently unclear.…”
Section: Defects In Blood-brain Barrier Transporters That May Contribmentioning
confidence: 99%
“…Furthermore, Pgp may function independently of LRP-1 by limiting the influx of blood-borne Ab into the brain. 67 The pathways governing influx will be described in the next section. The cellular prion protein 68 and the multidrug transporters ABCG2 and 4 have also been shown to contribute to Ab efflux across the BBB, 69 although AD-relevant changes of these are presently unclear.…”
Section: Defects In Blood-brain Barrier Transporters That May Contribmentioning
confidence: 99%
“…The results demonstrated ABCG2 to restrict the apical-to-basolateral permeability of Aβ isoforms, suggesting a role for this efflux transporter in preventing bloodborne Aβ peptides from entering the brain, but not in transporting the brain Aβ into blood. 62,63,124,125 Unlike ABCB1, expression analyses of 273 BBB-related genes performed by Xiong and colleagues showed that ABCG2 gene was significantly up-regulated in the brains of AD and CAA patients compared to age matched control group. 124 The authors explained ABCG2 gene up-regulation as a compensatory mechanism initiated by the pathological microenvironment in the neurovascular unit to reduce Aβ burden in the brain by preventing access of circulatory Aβ into the brain, or as an early vascular change involved in maintaining circulatory pool of Aβ and thus preventing Aβ clearance from perivascular or parenchymal pools.…”
Section: ■ Abcg Family Abcg2 (Breast Cancer Resistance Protein Bcrp)mentioning
confidence: 99%
“…Enfin, une augmentation de l'expression de RAGE est observée au niveau des microvaisseaux des patients atteints de la maladie d'Alzheimer [8,15]. Nous avons utilisé un modèle de BHE reproduisant in vitro les caractéristiques majeures de la BHE in vivo [6], et avons mis en évidence dans ce modèle la pré-sence exclusive de ce récepteur sur la face luminale (en contact avec le compartiment sanguin) des CEC [16]. En utilisant un inhibiteur compétitif de RAGE, nous avons démontré qu'il est capable d'intervenir dans l'influx de peptides A sans qu'aucune protéolyse ne soit observée.…”
Section: Rage Et L'influx Des Peptides Abunclassified
“…L'ensemble de ces données suggère que les cellules endothéliales joueraient également un rôle dans la dégradation des peptides A cérébraux et que ces mécanismes de dégradation seraient moins efficaces lors de la maladie, contribuant ainsi à l'accumulation cérébrale de ces peptides. [16]. RAGE semble donc exclusivement impliqué dans l'influx des peptides A et un essai clinique utilisant un inhibiteur de ce récepteur est actuellement envisagé [17].…”
Section: Rôle Des Cec Dans La Dégradation Des Peptides Abunclassified
See 1 more Smart Citation